PEMANFAATAN ENZIM RENNET dan Lactobacillus plantarum YN 1.3 TERHADAP pH, CURD dan TOTAL PADATAN KEJU - Budiman, Stevani; Hadju, R.; Siswosubroto, S.E.; Rembet, G.D.G. (Universitas Sam Ratulangi, 2017)
UTILIZATION of RENNET ENZYME and Lactobacillus plantarum YN 1.3 ON pH, CHEESE SOLIDS TOTAL and CURD. The aims of thisresearch was to know the rennet enzyme levels and utilization of Â Lactobacillus plantarum YN 1.3 on Cheese pH, solids total and curd. This research designed by a Completely Randomized Design, the treatments were the rennet enzyme levels and Lactobacillus plantarum YN 1.3. Each treatments has four times replications. The data obtained were analyzed using SPSS ver 20 tools and significant effects was test by Tukey HSD. The results of this research showed no significant difference (p > 0.05) on cheese pH.Â Cheese solids total and curd has highly significant difference effects (p < 0,01). Based on the discussion and data analysis, can be concluded that the utilization of the rennet enzyme level 2% and Lactobacillus plantarum YN 1.3 8% produced good performs of pH, total cheese solids and curd.Key words: cheese, rennet enzyme and Lactobacillus plantarum YN 1.3